SUSTAINABLE MOBILITY INDICATORS FOR CITIES - Branza, Gratiela (Ecoforum Journal, 2023)
Abstract The development of every nation is measured through its grade of industrialization and especially its transportation system development. But this development can only be achieved by respecting and fulfilling the goals of sustainable mobility. This paper presents the concept of sustainable mobility and the specific set of sustainable mobility indicators for cities, that are used to analyze, evaluate and improve urban policies in the sphere of sustainable mobility. The paper also includes a brief comparison between the country with the highest score and the one with the lowest score in the global ranking, depending on the value of the GSMI score. Since Sweden is the leader of the European countries in sustainable mobility, the paper also highlights some examples of good practices in the field of sustainable mobility promoted by Swedish companies.